HUBUNGAN LINGKAR PINGGANG DENGAN KADAR GULA DARAH PADA PENDERITA DIABETES MELITUS TIPE 2 DI PUSKESMAS BOTANIA KOTA BATAM - Dyah Marianingrum; Ibrahim , (Universitas Batam, 2019)
According to the 2017 International Diabetes Federation, the global prevalence rate of Diabetes Mellitus sufferers of 8.8% of the total population in the world from year to year shows an increase. The number of deaths that occurred as many as 4 million people in 2017. The western Pacific region including Indonesia has the highest mortality rate compared to all regions with a mortality rate of 1.3 million in adults. This shows the awareness of the sufferers of Diabetes Mellitus for routine check-ups to health centers is still lacking. According to the 2013 Basic Health Research, the prevalence of people with diabetes mellitus in Indonesia based on a diagnosis or symptoms of 2.1% increased from previous research of 1.1%. The prevalence of DM in Riau Islands Province increased from 0.8 to 1.5%. According to Batam City Health Office data in 2016, the incidence of Diabetes Mellitus in several Puskesmas with 3,724 visits, Botania Puskesmas was the third highest after Lubuk Baja and Balik Padang. This study used a survey method with a cross-sectional approach. The population in this study was Type 2 diabetes mellitus patients who examined themselves at the Botania Health Center in Batam City. Sampling using a purposive sampling technique with criteria established by researchers. The dependent variable in this study is blood sugar level because it is a diagnosis of diabetes mellitus while the independent variable is the measurement of waist circumference. Data analysis using the Spearman rank test. The results of the univariate analysis showed 73.7% of the majority of respondents had a high sugar level. Bivariate analysis with the Spearman Rank test, the results of the analysis found there is a relationship between waist circumference size and blood sugar levels (P-value = 0.341) with the direction of a positive relationship and the strength of the relationship is sufficient (r = 0.409). There is a significant relationship between waist circumference size and blood sugar level with sufficient strength of a relationship